Analysis of the Influence of Infrastructure on Economic Growth in Central Sulawesi Province - Fuji Oktaviani; Muhtar Lutfi; Rita Suirlan; Mukhtar Tallesang; Vera Sri Endah Cicilia (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
This study aims to analyze the influence of road and electricity infrastructure on economic growth in Central Sulawesi Province from 2019 to 2023. The descriptive research method uses secondary data from 13 districts/cities in Central Sulawesi Province. This study uses panel data regression analysis. The results show that road infrastructure and electricity infrastructure have a positive and significant effect on economic growth in Central Sulawesi Province. Positive values ​​​​in both variables indicate that each percentage increase in road infrastructure and electricity infrastructure will increase economic growth by less than 1 percent. The greater the development of road infrastructure and electricity infrastructure, the greater the rate of economic growth in Central Sulawesi Province. Road infrastructure encourages smooth economic activities, while electricity infrastructure contributes to increasing GRDP through increased productivity and economic activity in various sectors.